THE INFLUENCE OF GOVERNMENT GOVERNANCE, PUBLIC INFORMATION DISCLOSURE, AND REGIONAL FINANCIAL INFORMATION SYSTEM ON THE PERFORMANCE OF LOCAL GOVERNMENT AGENCIES IN PASER REGENCY - Muhammad Harits Zidni Khatib Ramadhani; Asmadhini Handayani Rahmah; Rezki Ananda Basid (PT. Radja Intercontinental Publishing, 2026)
This study aims to examine and analyze the influence of Government Governance, Public Information Disclosure, and the Regional Financial Information System (SIKD) on the Performance of Local Government Agencies in Paser Regency, both partially and simultaneously. The background of this research is grounded in the realization of Paser Regency's Own-Source Revenue (PAD) in the 2025 fiscal year, which reached only 79.36% of the established target, as well as the inconsistency of findings in previous studies regarding the variables that affect local government performance. This research is theoretically grounded in stewardship theory, which conceptualizes the government as a steward entrusted with managing public resources in the best interest of the community as the principal. This study employs a quantitative approach through a survey method using questionnaire distribution. The study population consisted of all employees of local government agencies in Paser Regency, with a sample of 151 respondents selected through purposive sampling from the Regional Financial and Asset Management Agency (BKAD) and the Regional Revenue Agency (Bapenda) of Paser Regency. The research instrument employed a four-point Likert scale. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method via SmartPLS 4. Validity was assessed through convergent validity (outer loadings > 0.7 and AVE > 0.5) and discriminant validity (HTMT < 0.85), while reliability was evaluated using Cronbach's Alpha and composite reliability. The findings indicate that: (1) Government Governance has a positive and significant effect on the Performance of Local Government Agencies in Paser Regency; (2) Public Information Disclosure has a positive and significant effect on the Performance of Local Government Agencies in Paser Regency; (3) the Regional Financial Information System has a positive and significant effect on the Performance of Local Government Agencies in Paser Regency; and (4) Government Governance, Public Information Disclosure, and the Regional Financial Information System simultaneously have a positive and significant effect on the Performance of Local Government Agencies in Paser Regency. These findings imply that improving the performance of local government agencies in Paser Regency requires the simultaneous strengthening of governance accountability, public information transparency, and the quality of the regional financial information system.